Papal jurisprudence, 385-1234 social origins and medieval reception of canon law - D'Avray, D. L. 1952- (Cambridge Cambridge University Press, 2022)
Explains the rise in demand for papal judgments from the 4th century to the 13th century, and how these decretals were later understood.
Cover -- Half-title page -- Title page -- Copyright page -- Dedication -- Contents -- Acknowledgements -- List of Abbreviations -- Sigla -- Introduction -- 1 Transformations and Long-Term Explanations -- 2 The Christian Roman Empire, c. 400 -- 3 c. 400: Practical Complexities and Uncertainties -- 4 c. 400: Uncertainty about Grace -- 5 Papal Rulings and Ritual -- 6 Hierarchies -- 7 Clerical Status and Monks -- 8 Returning Heretics -- 9 Pelagianism and the Papacy -- 10 Leo I -- 11 Post-Imperial Syntheses -- 12 Early Papal Laws in the Barbarian West -- 13 Carolingian Culture and Its Legacy -- 14 1050-1150 -- 15 Theology and Law -- 16 c. 400 and c. 1200: Complexity, Conversion, and Bigamia -- 17 Clerics in Minor Orders -- 18 Choosing Bishops -- Overall Conclusions -- Appendix A Leo I -- Appendix B Gelasius I -- Appendix C Gloss II (Johannes Teutonicus and Bartholomaeus Brixiensis) on Gratian and the Liber Extra -- Appendix D Conceptual Sources -- Select Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Canon Law -- History -- Middle Ages, 600-1500; Canon Law -- Reception; Electronic books